Sociodemographic determinants of knowledge and attitude in the primary prevention of cervical cancer among University Tunku Abdul Rahman (UTAR) students in Malaysia: preliminary study of HPV vaccination - Tusimin, Maiza; Chek, Lo Yee; Abdul Razak, Nur Zarifah Syahmi; Zainol, Mohamad Izwan; Minhat, Halimatus; Rejali, Zulida (BioMed Central, 2019)
Background: Cervical cancer is the third most common cancer affecting women around the world in which the Human Papillomavirus (HPV) is the one of the recognized causative agent affecting women health. In response to this health issue, the Malaysian government had officially implemented the HPV immunisation programme for secondary schoolchildren in 2010 at the age of 13 years old and above. The purpose of this study is to investigate the sociodemographic determinants of knowledge and attitude among students of Universiti Tunku Abdul Rahman (UTAR) towards the HPV vaccination programme. Methods: A cross-sectional study was conducted using self-administered questionnaires, recruiting 374 UTAR's students as the respondents by using convenience sampling method. Respondents were categorized as having good/poor level of knowledge and positive/negative attitude towards HPV vaccination. Results: Over half of the respondents were females (64.5%) and the majority were aged 20 years old and below (55.8%). Generally, 54.7% of the total respondents had a high level of knowledge towards HPV vaccine while 57.5% of the total respondents showed a negative attitude towards HPV vaccine. Female respondents aged 20 years old and below showed good knowledge (56.4%) and a more positive attitude (55.8%) towards HPV vaccine. Students from the Faculty of Medicine and Health Sciences (FMHS) exhibited higher knowledge (67.3%) and positive attitude (62.4%) as compared to the Faculty of Accountancy and Management (FAM) which showed only 32.7% of knowledge and 37.6% of positive attitude towards the HPV vaccination. Conclusion: The majority of UTAR students possess good knowledge regarding HPV vaccination. Nonetheless, they demonstrated a negative attitude towards HPV vaccination, depicting the necessity to impart and further intensify the sense of health awareness among all students, especially among male students. The judicious use of social media apart from the conventional mass media should be an advantage as to enhance the practice of HPV vaccination among them and thereafter minimize the health and economic burdens of cervical cancer.